pH Sensitive graft copolymers for zero order drug release: a mechanistic analysis - Muthusamy, Ramesh; Kulkarni, Mohan Gopalkrishna (Drug Development and Industrial Pharmacy, 2012)
Aliphatic polyesters containing pendent unsaturation were synthesized by the polycondensation of a diol, dicarboxylic acid and glycidyl methacrylate. Grafting methacrylic acid (MAA) resulted in graft copolymers containing polyester backbone and MAA grafts. Depending on composition, the polymers swelled extensively and eroded or dissolved at near neutral pH but remained in collapsed state at acidic pH. Three representative drugs differing in solubility, viz., Diltiazem hydrochloride (DH), Indomethacin (IM) and Verapamil hydrochloride (VH) were released at constant rate from tablets made by compressing spray-dried microparticles. The release of DH at constant rate has been attributed to increase in diffusion coefficient of the drug from the swollen layer of matrix. The release of IM and VH at constant rate was governed by erosion and was enhanced in matrices which undergo dissolution. The release rate was enhanced with increasing MAA content and the frequency of grafts along the polyester backbone. Once a day dosage forms for drugs differing in solubility have been developed using a single polymer matrix which is easy to manufacture.
Keywords: Diffusion; erosion; Graft copolymer; matrix tablets; microparticles; spray drying; sustained release